DEET, Active Substance Of Repellent That Effective And Safe For Travelers - Made Ika Lestari (Universitas Udayana, 2013)
Increased flow of tourism to the tropics and the changing patterns of vector-borne diseases require increased protection against insects. To prevent transmission of the disease is done several ways that increase self-protection by using mosquito repellent can protect travelers while outdoor activities. One option is active formula mosquito repellent DEET. The purpose of this paper is to determine the best dosage forms for travelers DEET., To determine the effectiveness and safety of DEET and to know the workings of the active ingredient DEET. The method of writing is the literature search through medical journals and articles. From the search was obtained, the most appropriate anti-mosquito travelers to use while on the move outdoors in the dosage form is DEET lotion applied to the skin as the most secure and durable because it does not easily evaporate. Mosquito repellent containing DEET has been proven effective and safe for use in adults, children, and pregnant women, but should still follow the instructions. The workings of the mosquito repellent DEET mosquito dispel is manipulating 1-Octen-3-ol used by mosquitoes to detect human presence. So ORN (olfactory receptor neurons) in the mosquitoes can not respond anymore to the maximum, so that people avoid the bites nyamuk.